Preparation of Carbon Nanotubes/TiO2 Composites with Multi-Walled Carbon Nanotubes and Titanium Alkoxides by Solvent Effect and Their Photocatalytic Activity - Oh, W.C.; Zhang, F.J.; Chen, M.L. (Asian Journal of Chemistry, 2010)
In this present paper, multi-walled carbon nanotubes (MWCNTs) are used as the starting material to prepare CNT/TiO2 composites with titanium alkoxides using different solvents. The composites were compre-hensively characterized by BET surface area measurements, scanning electron microscopy, transmission electron microscopy, X-ray diffraction, energy dispersive X-ray analysis and UV-vis absorption spectroscopy. The photoactivity of the prepared materials, under UV irradiation, was tested using the conversion of methylene blue from a model aqueous solution. Finally, according to the results of the methylene blue removal experiment, it can be considered that the removal of methylene blue by the CNT/TiO2 composites is not only due to the adsorption of the MWCNTs and photocatalytic degradation of TiO2, but also to the electron transfer between the MWCNTs and TiO2.